2012
DOI: 10.1524/zkri.2012.1504
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional pair distribution function analysis of disordered single crystals: basic concepts

Abstract: Abstract. Theory and principles of the three-dimensional pair distribution function analysis of disordered single crystals are introduced. The mathematical framework is presented and the appearance of pair distribution function patterns is discussed on the examples of some basic disorder models. It is further demonstrated how pair distribution function maps are affected by typical experimental problems. Approaches for a better understanding of such effects and strategies for a proper handling of artifacts in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
139
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 17 publications
4
139
0
Order By: Relevance
“…Looking forward, one particular challenge for the PDF community is the development of a more complete understanding of which problems are definitively solvable using PDF analysis and which are not. Recent developments such as (i) the 3D-∆PDF approach, 85 (ii) "dynamic" PDF measurements which can in principle separate static and vibrational contributions to G(r) peak broadening, 86,87 and/or (iii) the ability to incorporate additional data from a variety of experimental techniques during PDF analysis [88][89][90][91] offer a particular sense of optimism in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Looking forward, one particular challenge for the PDF community is the development of a more complete understanding of which problems are definitively solvable using PDF analysis and which are not. Recent developments such as (i) the 3D-∆PDF approach, 85 (ii) "dynamic" PDF measurements which can in principle separate static and vibrational contributions to G(r) peak broadening, 86,87 and/or (iii) the ability to incorporate additional data from a variety of experimental techniques during PDF analysis [88][89][90][91] offer a particular sense of optimism in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…As the hightemperature phase is cubic, the low-temperature phase can easily become twinned. We analyze these diffuse-scattering data using the threedimensional difference pair distribution function (3D-ÁPDF) method (Canut-Amoró s, 1967;Schaub et al, 2007;Weber et al, 2007;Weber & Simonov, 2012), which makes it possible to directly construct the two-dimensional superstructure of the layers as well as identify the one-dimensional disorder of the layer stacking. In 2017, Eikeland et al showed that the diffraction pattern of a very high quality single crystal of -Cu 2Àx Se can be divided into strong main reflections and weak superstructure reflections and was able to solve the average structure from the main peak intensities only (Eikeland et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, this difficulty is not enough to explain the problem of solving the structure. The 3D-ÁPDF is defined as the inverse Fourier transform of the scattered diffuse intensity, which is equal to the autocorrelation of the difference between the total electron density and the average periodic electron density (Weber & Simonov, 2012): This average structure contains ordered Se sites and Cu on disordered sites.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the diffuse intensities could be further optimized by using GPU processors to Fourier transform the scattering density of the disordered crystals as shown by Gutmann (2010). In addition, they may be combined with other modeling techniques, MC modeling (Proffen & Welberry, 1998) and three-dimensional PDF techniques (Weber & Simonov, 2012) in particular. The resulting local structure variations may then provide a basis for explaining structure-property relationships of disordered materials.…”
Section: Discussionmentioning
confidence: 99%